“The Wrong Migration:” The Problem of Managing Migration Flows in the Nordic Countries Politics - E. D. Pronyakina (Международная аналитика)
In the modern world, migration crises are likely to become commonplace. Denmark, Norway and Sweden are countries that attract migrants from both European and non-European countries. Today they face the diffi cult task of developing a common migration policy, which is hindered by a number of reasons: economic, ideological and political. The article attempts to assess the prospects for cooperation between the Scandinavian countries on migration issues in the near future. Based on the provisions of the Copenhagen School of Security, the author examines mass migration through the prism of the risks it poses to the culturally homogeneous societies of Denmark, Norway and Sweden, to the unique Scandinavian model of the welfare state and to Nordic Co-operation. Comparing the Nordic countries’ approaches to migration management, the author concludes that they are united by the excessive involvement of the state in the processes of adaptation and integration of migrants. Despite the fact that the migration policies of the three countries have undergone signifi cant changes since 2016, the emphasis is still on the management of quantitative indicators (through the issuance of residence permits or deportation) rather than on the creation of social partnerships between migrants and natives. In Danish, Norwegian and even Swedish society, the idea of the need to promote “right” (European) immigration and limit “wrong” (foreign cultural) immigration prevails. There is a situation in which the main integration eff orts are directed at those groups of immigrants who are already suffi ciently integrated. Non-European migrants, regardless of their professional qualifi cations or personal qualities, are still perceived as a threat to Nordic identity.